2018
DOI: 10.1021/acs.est.8b01494
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Polyfluoroalkylether Sulfonates Exhibit Similar Binding Potency and Activity to Thyroid Hormone Transport Proteins and Nuclear Receptors as Perfluorooctanesulfonate

Abstract: Chlorinated polyfluoroalkylether sulfonates (Cl-PFAESs) have been used as perfluorooctanesulfonate (PFOS) alternatives in the chrome plating industry for years. Although Cl-PFAESs have become ubiquitous environmental contaminants, knowledge on their toxicological mechanism remains very limited. We compared potential thyroid hormone (TH) disruption effects of Cl-PFAESs and PFOS via the mechanisms of competitive binding to TH transport proteins and activation of TH receptors (TRs). Fluorescence binding assays re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 42 publications
6
53
0
Order By: Relevance
“…This is in agreement with an in vitro study suggesting that PFASs inhibited GH3 cell (rat pituitary-derived cell line) proliferation, which is mediated by THR (Long et al, 2013). However, in vitro studies also using GH3 cells as well as THRA and THRB-mediated luciferase reporter assays suggest that the PFOS is THR agonist (Xin et al, 2018). The results of the relationships between transcript levels of THRA and RXRA in blubber plasma PFAS concentrations in the walruses should be interpreted with care.…”
Section: Accepted Manuscriptsupporting
confidence: 88%
“…This is in agreement with an in vitro study suggesting that PFASs inhibited GH3 cell (rat pituitary-derived cell line) proliferation, which is mediated by THR (Long et al, 2013). However, in vitro studies also using GH3 cells as well as THRA and THRB-mediated luciferase reporter assays suggest that the PFOS is THR agonist (Xin et al, 2018). The results of the relationships between transcript levels of THRA and RXRA in blubber plasma PFAS concentrations in the walruses should be interpreted with care.…”
Section: Accepted Manuscriptsupporting
confidence: 88%
“…48 Xin et al also observed a stronger binding potency for 6:2 Cl-PFESA than for PFOS to thyroid hormone transport proteins and a similar agonistic activity toward thyroid hormone receptors. 49 The binding parameters of PFOS to HSA have been reported in several studies. 26,28,29,50,51 The binding constant of PFOS in the present study is similar to that observed by Chen and Guo.…”
Section: ■ Discussionmentioning
confidence: 99%
“…An accumulation of PFOS and PFOA was documented in thyroid cells, and a cytotoxic effect was observed after exposure to extremely high concentrations of these compounds ( 37 ). In addition, PFOS and PFOA reduce thyroperoxidase (TPO) activity in tumor thyroid cells lines ( 38 ) and PFOS was suggested to act as a thyroid hormone receptor (THR) agonist in GH3 cells as found by using THRα and THRβ-mediated luciferase reporter assay ( 39 ). Interestingly, Conti et al., showed that PFOS (but not PFOA) is able to inhibit the iodide accumulation in FRTL-5 cells mediated by NIS.…”
Section: Introductionmentioning
confidence: 99%